2001
DOI: 10.1126/science.1058827
|View full text |Cite
|
Sign up to set email alerts
|

Glia-Synapse Interaction Through Ca 2+ -Permeable AMPA Receptors in Bergmann Glia

Abstract: Glial cells express a variety of neurotransmitter receptors. Notably, Bergmann glial cells in the cerebellum have Ca2+-permeable alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-type glutamate receptors (AMPARs) assembled without the GluR2 subunit. To elucidate the role of these Ca2+-permeable AMPARs, we converted them into Ca2+-impermeable receptors by adenoviral-mediated delivery of the GluR2 gene. This conversion retracted the glial processes ensheathing synapses on Purkinje cell dendritic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
305
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(320 citation statements)
references
References 20 publications
14
305
1
Order By: Relevance
“…In agreement with the previous reports, a subpopulation of GABAergic cells expressed one of EGF receptor subtypes, ErbB1, and bound to fluorescent-labeled EGF (Gómez-Pinilla et al, 1988;Kornblum et al, 1995). Moreover, the GluR1-reducing activity of TGFα was apparent not only in AMPA binding activity per milligram protein but also on per culture dish basis: If the mitotic activity of TGFα contributed to the change in AMPA binding, then glial proliferation should either not influence or increase AMPA binding per dish, because astrocytes also express functional AMPA receptors (Seifert and Steinhauser, 2001;Iino et al, 2001). The marked decrease in AMPA binding by TGFα ruled out this explanation.…”
Section: Distinction Between Mitotic Activity and Ampa Receptor-reducmentioning
confidence: 99%
“…In agreement with the previous reports, a subpopulation of GABAergic cells expressed one of EGF receptor subtypes, ErbB1, and bound to fluorescent-labeled EGF (Gómez-Pinilla et al, 1988;Kornblum et al, 1995). Moreover, the GluR1-reducing activity of TGFα was apparent not only in AMPA binding activity per milligram protein but also on per culture dish basis: If the mitotic activity of TGFα contributed to the change in AMPA binding, then glial proliferation should either not influence or increase AMPA binding per dish, because astrocytes also express functional AMPA receptors (Seifert and Steinhauser, 2001;Iino et al, 2001). The marked decrease in AMPA binding by TGFα ruled out this explanation.…”
Section: Distinction Between Mitotic Activity and Ampa Receptor-reducmentioning
confidence: 99%
“…To look for the physiological impact of the Ca 2þ permeable glial receptors they were made Ca 2þ impermeable through viral overexpression of the GluA2 subunit. As a result, the fine lamellae of Bergmann glial cells underwent profound changes: synapse ensheathment was lost, glutamate clearance of the synaptic cleft was impaired and Purkinje cells were now innervated by more than one climbing fibre [8]. Full ablation of AMPA receptors (GluA1 and GluA4) from Bergmann glial cells led to retraction of processes from the synapses, disturbed glutamate buffering and altered synaptic transmission between parallel fibres and Purkinje cells.…”
Section: Introductionmentioning
confidence: 99%
“…mGluR1 and mGluR5 are coupled to phosphoinositide hydrolysis, whereas other mGluRs are primarily coupled to a downregulation of cAMP formation (Nakanishi, 1992). Several studies have demonstrated expression of some of iGluR subunits in astrocytes, and the expression appears to vary among brain regions (Burnashev et al, 1992;Steinhauser and Gallo, 1996;Iino et al, 2001). Electrophysiologic studies of astrocytes support a functional role for some of the iGluR subtypes (Burnashev et al, 1992;Muller et al, 1992Muller et al, , 1997Holzwarth et al, 1994;Robert and Magistretti, 1997;Schipke et al, 2001).…”
Section: Introductionmentioning
confidence: 99%